A foot/ground contact model for biomechanical inverse dynamics analysis - Van Hulle, R.; Schwartz, C.; Denoël, V.; Croisier, J.-L.; Forthomme, B.; Brüls, O. (Journal of Biomechanics, 2020)
• Numerical method for estimation of ground reaction forces. • Unilateral contact model expressed at the center of pressure. • Foot/ground reaction forces modelled by unilateral Lagrange multipliers. • Indeterminacy in the force estimation handled using a least square approach with filtering.